An Investigation on the Relationship between Facial Emotional Recognition and Tendency to Commit Crime; Moderating the Effects of Socio-Economic Well- Being (Global Journal of Human-Social Science, 2020)
Abstract not found
Keywords: facial emotional recognition; tendency to commit crime; socio-economic well-being